Taking Culture into Account: A Maori Perspective on Visual Impairment - Bevan-Brown, Jill; Walker, Taingunguru (Journal of visual impairment & blindness, 2013)
Some barriers were related to studying Maori subjects, while others were of a more general nature.\n Cultural suggestions The participants believed that Maori children who are visually impaired should be given the opportunity to be fully involved in cultural activities, such as kapa haka (Maori performing arts) and learning the Maori language from kohanga reo (total-immersion early childhood centers) upward if they so chose. [...]community members, including people from the visually impaired person's own ethnic group, should ask themselves: "Are people being denied access to community and cultural activities and experiences because of their visual impairment, and, if so, what needs to be done to change this situation?"